2009
DOI: 10.1258/acb.2008.008094
|View full text |Cite
|
Sign up to set email alerts
|

Family tracing to identify patients with Familial Hypercholesterolaemia: the second Audit of the Department of Health Familial Hypercholesterolaemia Cascade Testing Project

Abstract: Cascade testing for FH in the UK is feasible, acceptable and likely to be cost-effective if it is a routine aspect of clinical care. However, national implementation would require an integrated infrastructure, so that all individuals have access to testing, and specialist services for the management of young people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 27 publications
2
59
0
Order By: Relevance
“…Direct FH cascading screening has recently been trialled in the UK (Hadfield et al 2009); in line with findings from an earlier review of the Dutch FH programme (UmansEckenhausen et al 2001), it was found that systematic family tracing by trained personnel plus direct clinical contact results in significantly more relatives coming forward for cholesterol screening (Hadfield et al 2009). Direct approaches have also been supported on the grounds that they may help overcome patients' reticence to disclose/ distribute information (Suthers et al 2006) and thus maximise the number of relatives approached and captured in the cascade.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Direct FH cascading screening has recently been trialled in the UK (Hadfield et al 2009); in line with findings from an earlier review of the Dutch FH programme (UmansEckenhausen et al 2001), it was found that systematic family tracing by trained personnel plus direct clinical contact results in significantly more relatives coming forward for cholesterol screening (Hadfield et al 2009). Direct approaches have also been supported on the grounds that they may help overcome patients' reticence to disclose/ distribute information (Suthers et al 2006) and thus maximise the number of relatives approached and captured in the cascade.…”
Section: Introductionmentioning
confidence: 66%
“…Empirical research suggests that direct contact by a member of the clinical team maximises the numbers of family members coming forward for FH screening (Umans-Eckenhausen et al 2001;Hadfield et al 2009); however, it also raises ethical issues. For example, an earlier Dutch study of FH cascading reported that 20% of family members approached reported feeling under pressure to have DNA testing following direct clinical contact (van Maarle et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family members who consent to being assessed for FH should be offered a standard plasma lipid profile and a genetic test if the family mutation is known and DNA testing available [6,8,78,80]. All individuals with potential FH should be made aware and understand the implications of genetic testing for certain types of insurance cover [8,81].…”
Section: Contacting and Informing Familiesmentioning
confidence: 99%
“…Using targeted gene sequencing, the observed detection rate of FH in relatives ranged from 53% to 56% in two studies, 37,45 which is broadly consistent with rates reported by others (37-56%; see Appendix 18). 11,19,67,[83][84][85] A study by Wiegman and colleagues 50 reported that a high detection rate (77%) in children from families in whom a mutation was identified in probands was observed through targeted sequencing. However, the authors of the study suggested that one possible reason for the high detection rate was that siblings with very low LDL-C levels were not taken to the clinic to undergo targeted sequencing.…”
Section: Cascade Testingmentioning
confidence: 99%